Fair Weather Neutron Bursts From Photonuclear Reactions by Extensive Air Shower Core Interactions in the Ground and Implications for Terrestrial Gamma‐ray Flash Signatures. Issue 6 (26th March 2021) - Bowers, Gregory S.; Shao, Xuan‐Min; Blaine, William; Dingus, Brenda; Smith, David M.; Chaffin, Jeff; Ortberg, John; Rassoul, Hamid K.; Ho, Cheng; Nellen, Lukas; Fraija, Nissim; Alvarez, C.; et al.
Abstract: We report on anomalously long duration (2 ms) count rate bursts following the impact of cosmic ray showers near a 7.62 cm x⊘7.62 cm LaBr3 scintillation detector at the High Altitude Water Cherenkov array in Mexico, previously described by Stenkin et al. (2001), and termed "neutron bursts." The largest burst produced 198 counts within 2 ms in our LaBr3 detector. We simulate the neutron burst albedo flux (that is, secondary emissions from an extensive air shower core impacting the ground), and show that (1) the characteristic spectra and count rates are well explained by neutron absorption in the ground and (2) any cosmic ray secondary that produces neutrons, either through hadron inelastic collisions, or photoneutron production by gamma‐rays, produces the same characteristic spectra. This implies that other natural phenomena that produce downward beams of gamma‐rays, like Terrestrial gamma ray flashes, should produce a similar "neutron burst" signature from the photoneutron reactions occurring in the soil. Plain Language Summary: When very large cosmic ray showers (CRS) impact the ground, neutrons are produced in the soil that will rattle around until they become captured by soil particles and release energetic gamma‐rays. This produces a slow explosion of particles emanating from the ground following a CRS impact, and is termed a 'neutron burst'. We present recent observations of neutron bursts from a hand held sized gamma‐ray detector at the High Altitude Water Cherenkov (HAWC) array in Mexico, that exhibit interesting spectral features (the presence of positron annihilation), and an interesting time structure (hundreds of counts within a few ms). Our simulations indicate that Terrestrial gamma‐ray flashes (TGFs, bursts of gamma‐rays associated with lightning) should also produce these neutron bursts. An implication of this work is that existing deployments of ground based TGF instruments, comprised of small gamma‐ray detectors, can additionally be used to observe signatures of large cosmic ray showers on clear days. Key Points: We report on fairweather count rate bursts with 2 ms duration following the impact of a large cosmic ray shower near a small scintillation detector at HAWC Simulations show that the spectra and decay time can be produced by either hadronic interactions, or photoneutron reactions from gamma‐rays These results imply that downward TGFs could produce a similar delayed neutron signature in the soil near ground based detectors